Projecting wheat demand in China and India for 2030 and 2050: Implications for food security - Abdul Mottaleb, Khondoker; Kruseman, Gideon; Frija, Aymen; Sonder, Kai; Lopez-Ridaura, Santiago (Frontiers Media, 2023)
The combined populations of China and India were 2.78 billion in 2020, representing 36% of the world population (7.75 billion). Wheat is the second most important staple grain in both China and India. In 2019, the aggregate wheat consumption in China was 96.4 million ton and in India it was 82.5 million ton, together it was more than 35% of the world's wheat that year. In China, in 2050, the projected population will be 1294–1515 million, and in India, it is projected to be 14.89–1793 million, under the low and high-fertility rate assumptions. A question arises as to, what will be aggregate demand for wheat in China and India in 2030 and 2050?